Pengembangan LKPD Berbasis SETS (Science, Environment, Technology and Society) Pada Pokok Bahasan Kesetimbangan Ion dan pH Larutan Penyangga Kelas XI SMA/MA Sederajat - Amelia Fatika Putri; Herdini Herdini; Roza Linda (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to produce a student worksheet based SETS on a valid ion balance and pH of buffer solutions for class XI SMA/MA and knows user’s response. This research is development research (R&D) that adapts the 4-D development model. The data collection instruments used in the form of validation sheets and user response questionnaires. The research results showed that the percentage of appropriateness of content, SETS characteristics, language and presentation was 91.66; 97.91; 89.58 and 91.67%. with valid criteria. One-on-one trials were carried out on 3 students with different abilities to get comments that were used to improve the student worksheet. The results of teacher and student responses were respectively 97.17% and 84.34% with very good criteria